2005
DOI: 10.1534/genetics.105.045849
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Spectral Tuning in the Violet-Sensitive Visual Pigment of African Clawed Frog, Xenopus laevis

Abstract: Ultraviolet (UV) and violet vision in vertebrates is mediated by UV and violet visual pigments that absorb light maximally (l max ) at 360 and 390-440 nm, respectively. So far, a total of 11 amino acid sites only in transmembrane (TM) helices I-III are known to be involved in the functional differentiation of these short wavelength-sensitive type 1 (SWS1) pigments. Here, we have constructed chimeric pigments between the violet pigment of African clawed frog (Xenopus laevis) and its ancestral UV pigment. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 32 publications
(53 reference statements)
1
64
0
Order By: Relevance
“…They include sites 83, 122, 211, 261, 265, 292, and 295 in RH1 pigments (e. g. Yokoyama, 2000a), sites 49, 122 and 207 in RH2 pigments (Yokoyama et al, 1999;Chinen et al, 2005a), sites 46, 49, 52, 86, 90, 91, 93, 97, 109, 113, 114, 116, and118 in SWS1 pigments (e. g. Yokoyama, 2000a;Babu et al, 2001;Shi and Yokoyama, 2003;Fasick et al, 2002;Takahashi and Yokoyama, 2005), sites 91, 94, 116, 122, 261, 292, and 295 in SWS2 pigments (Takahashi and Ebrey, 2003;Chinen et al, 2005b), and sites 164, 181, 261, 269, and 292 in M/LWS pigments, which correspond to sites180, 197, 277, 285, and 308 of the human red-and greensensitive pigments . Our analyses of the bluefin killifish SWS2 pigments show that site 44 is also involved in the spectral tuning of visual pigments, increasing the total number of critical amino acid sites to 26.…”
Section: Discussionmentioning
confidence: 99%
“…They include sites 83, 122, 211, 261, 265, 292, and 295 in RH1 pigments (e. g. Yokoyama, 2000a), sites 49, 122 and 207 in RH2 pigments (Yokoyama et al, 1999;Chinen et al, 2005a), sites 46, 49, 52, 86, 90, 91, 93, 97, 109, 113, 114, 116, and118 in SWS1 pigments (e. g. Yokoyama, 2000a;Babu et al, 2001;Shi and Yokoyama, 2003;Fasick et al, 2002;Takahashi and Yokoyama, 2005), sites 91, 94, 116, 122, 261, 292, and 295 in SWS2 pigments (Takahashi and Ebrey, 2003;Chinen et al, 2005b), and sites 164, 181, 261, 269, and 292 in M/LWS pigments, which correspond to sites180, 197, 277, 285, and 308 of the human red-and greensensitive pigments . Our analyses of the bluefin killifish SWS2 pigments show that site 44 is also involved in the spectral tuning of visual pigments, increasing the total number of critical amino acid sites to 26.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the only difference between A. carolinensis and lacertids corresponds to the replacement V109I, which is identical to that found in Gekko gecko, where UV vision has also been confirmed using MSP (λ max =364 nm; Table 1). Moreover, sitedirected mutagenesis has suggested that the V109A substitution produces a shift in the λ max of the resulting visual pigment of only 1 nm [from 359 nm in the ancestral pigment to 360 nm in the mutant (Takahashi and Yokoyama, 2005)]. …”
Section: Characterization Of Oil Dropletsmentioning
confidence: 99%
“…We amplified exon 1 of the SWS1 opsin gene (292 nucleotides with primers, 256 nucleotides without primers) because this fragment encompasses the 13 amino acid positions relevant for UV vision: F46, F49, T52, F86, S90, V91, T93, A97, I109, E113, A114, L116 and S118 [numbers are standardized by those of the bovine rhodopsin (Shi and Yokoyama, 2003;Takahashi and Yokoyama, 2005;Yokoyama, 2008)]. We designed degenerate PCR primers based on the sequences coding for the SWS1 opsin gene from Anolis carolinensis (GenBank accession no.…”
Section: Spectral Tuning Of the Sws1 Opsinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to achieve these goals, we are faced with two major problems. First, certain amino acid changes at 13 sites are known to shift the max s of SWS1 pigments to date (5,(9)(10)(11)(12)(13)(14), but it is a daunting task to identify other critical amino acid changes because their effects on the max -shift are often not detectible when they are studied individually (9,15,16). Second, and perhaps more disturbingly, no violet-sensitive SWS1 pigment has been isolated from fish (17).…”
mentioning
confidence: 99%